EVALUASI USABILITY WEBSITE SPMB DI SMPN 4 SAMARINDA MENGGUNAKAN SYSTEM USABILITY SCALE - Indri; Ramadiani, Ramadiani; Sudarman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to evaluate the usability of a website using the System Usability Scale (SUS) as a basis for identifying aspects that require improvement. Data were collected by distributing the SUS questionnaire, which consists of 10 statements rated on a five-point Likert scale, to nine respondents who were website users. The data were analyzed by converting the responses according to the SUS scoring procedure, calculating the final SUS score, and interpreting the results based on the acceptability, grade scale, and adjective ratings categories. The findings indicated that the website achieved a SUS score within the Good category, placing it in the acceptable range and demonstrating a satisfactory level of usability. Most respondents reported that the website was easy to use, the available features were well integrated, and the system effectively supported task completion. Nevertheless, several aspects still require improvement, particularly in helping users remember how to use the system after a period of inactivity and in enhancing the consistency of the user interface. Therefore, future website development should focus on simplifying navigation, improving interface consistency, optimizing the menu structure, and providing more informative user guidance to enhance user experience and ensure continuous improvement in website service quality.